Immunological aspects of COVID-19: what we know so far (Bangladesh Journal of Medicine, 2021)
The newly emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the disease that it causes coronavirus disease 2019 (COVID19) have changed the world. Many virulence factors and immune mechanisms contribute to the deteriorating effects during SARS-CoV-2 infection. Both humoral and cellular immune responses are involved in the pathophysiology of the disease. The clinical picture of COVID-19, immune memory and reinfection remains unclear and unpredictable. An electronic search of PubMed, Cochrane Library and Google scholar was performed, and citation relevance was determined according to the aim of the review.Other relevant literature was manually searched as compliment. More than 60 relevant scientific articles and reports were considered. We have reviewed the literature describing immunological aspects of COVID-19.Through this review, we tried to explain theimmune pathogenesis of SARS CoV 2infection providing high-quality evidence to understand SARS-CoV-2 pathophysiology, its interaction with target cells and the immune response to the virus, including the contribution of dysfunctional immune responses to disease progression in patients with COVID-19, based on the recent research progress of SARS CoV 2 and the knowledge from researches on SARS CoV and MERS CoV. Different therapeutic options have been implemented to find effective, even though not specific, treatment to the disease, many hopes are put in developing an effective vaccine against the virus. Understanding the immunopathogenesis of COVID-19 may provide important clues for effective vaccine and treatments of this disease.Bangladesh J Medicine January 2021; 32(1) : 43-52